Investigation and analysis of two-layer spoke-type ferrite interior permanent magnet machine - Abdurahem, Hayder Abdulhasan (Cranfield University, 2019)
A Novel two-layer spoke-type ferrite IPM design is presented based on a commercial induction motor as a low-cost high-performance alternative for new installation to meet efficiency requirements “greener” for various variable speed applications. The proposed design improves PM flux by flux-focusing techniques and maximises the reluctance torque with a two-layer structure. High torque density and efficiency are achieved with comparable performance to a rare-earth equivalent. At first, two-Dimensional d-q frame analytical methods are developed based on the magnetic circuit models. Then, FEA models of the ferrite and induction motors are built and analysed. A comprehensive investigation is carried out focusing on the performances in terms of torque profiles, losses, efficiency and power factor. The influences of temperature variation and distribution on the performance of novel two-layer spoke-type interior permanent magnet machines under different operating conditions are analysed. The analysis is based on a developed thermal circuit model. For benchmarking, a standard industrial IM is used. “Comprehensive experimental tests are undertaken, and the results show the proposed ferrite IPM machine has distinctive advantages over the IM in terms of efficiency, power density and speed range. In addition, due to low cost ferrite materials, it has a comparable price advantage. Finally, A prototype machine with the proposed design is manufactured, and both the two motors are tested under various operating conditions. The experimental results confirm the FEA simulations and validate superior performance of the proposed ferrite motor over its induction counterpart.
Economou, John - Associate Supervisor
Keywords: Ferrite; analytical model; induction machine; low cost; high efficiency; torque profiles